Demand for housing and urban services in Brazil: A hedonic approach - Maria da Piedade Morais; Bruno de Oliveira Cruz (Institute for Applied Economic Research (ipea), 2015)
This paper seeks to estimate the demand for housing and urban services in the major Brazilian metropolitan areas (MAs), as a contribution for the formulation of public policies of urban development. The theoretical approach used is the hedonic prices model (Rosen, 1974), which relates price with the property characteristics. The data was obtained from the 1997 National Household Survey (Pnad), published by the Brazilian Institute of Geography and Statistics (IBGE), encompassing 10 MAs. We have verified that the provision of proper housing and urban infrastructure services can significantly increase property prices in metropolitan areas, implying that such policies may have strong redistributive impacts and can be used to fight urban poverty in Brazil. Among the MAs studied, S\~ao Paulo presented the highest average rent, independently of the characteristics of the properties. The importance of the present study resides in trying to evaluate the impact of the governmental urban policies through regression analysis, what would allow policy makers to obtain more detailed information on the nature of housing demand - regarding the consumers' preferences for the different attributes of the house and levels of provision of urban services - as well as on the capacity of cost-recovery, and the social impacts of the different housing, sanitation and urban development programs.
Keywords: 330